Preparation method and application of self-supporting nickel-based alloy catalyst
A self-supporting nickel-based alloy catalyst with enhanced surface area and activity addresses poor electrolysis performance in AEM systems, facilitating efficient hydrogen production through automated synthesis.
Patent Information
- Application Number
- CN202410582436.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-05-11
- Publication Date
- 2024-12-13
- Estimated Expiration
- 2044-05-11
AI Technical Summary
Existing alkaline water electrolysis technologies face poor water electrolysis performance and high energy consumption, necessitating the development of more active catalysts for improved electrode activity, particularly in AEM systems.
A self-supporting nickel-based alloy catalyst with a porous macrostructure and lamellar microstructure is synthesized using nickel and aluminum salts, facilitated by an electrochemical synthesis chamber for automatic operation, enhancing specific surface area and catalytic activity.
The catalyst achieves high catalytic activity and selectivity, reducing manual operation difficulty and ensuring uniformity and efficiency in AEM electrolysis, with improved hydrogen production and reduced energy consumption.
Smart Images

Figure CN118460880B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of material science, and more particularly to a preparation method and application of a self-supporting nickel-based alloy catalyst. Background Art
[0002] The self-supporting nickel-based alloy catalyst is a multi-element alloy system composed of metal elements such as nickel and aluminum. It not only has good mechanical stability and thermal stability, but also has excellent corrosion resistance, which enables it to maintain stable catalytic performance under high temperature, high pressure and corrosive environment. The porous structure provides a large number of active sites for the catalytic reaction. The high-density distribution of these active sites helps to improve the conversion efficiency of the reactants. At the same time, its high specific surface area further enhances the contact area with the reactants and promotes the increase of the reaction rate. In terms of catalytic performance, the self-supporting nickel-based alloy catalyst exhibits extremely high activity and selectivity.
[0003] However, in alkaline water electrolysis technology, porous nickel-based electrodes are generally used to catalyze the water electrolysis reaction, but the water electrolysis performance is poor and the energy consumption of hydrogen production is high. In order to improve the electrode reaction activity, other metals are doped on the basis of nickel electrodes to form alloy electrodes, which improves the reaction activity to a certain extent. In the latest AEM water electrolysis technology, higher requirements are placed on the catalytic activity of the electrode, and it is necessary to develop more active catalysts to highlight the advantages of AEM.
[0004] Therefore, the present invention discloses a preparation method and application of a self-supporting nickel-based alloy catalyst, which is simple to operate, easy to synthesize on a large scale, and has low cost for non-precious metals; the synthesized catalyst has a porous structure at a macroscopic level and a lamellar structure at a microscopic level, which greatly increases the specific surface area of the catalyst and has extremely high catalytic activity; the self-supporting electrode structure can be directly used in AEM water electrolysis to produce hydrogen, which is simple and convenient. Summary of the invention
[0005] In view of the deficiencies in the prior art, the present invention discloses a preparation method and application of a self-supporting nickel-based alloy catalyst, which is simple to operate, easy to synthesize on a large scale, and has low cost for non-precious metals; the synthesized catalyst is macroscopically porous and microscopically lamellar, which greatly increases the specific surface area of the catalyst and has extremely high catalytic activity; the self-supporting electrode structure can be directly used in AEM electrolysis of water to produce hydrogen, which is simple and convenient. At the same time, an electrochemical synthesis chamber is used to achieve automatic synthesis and intelligent operation, which greatly reduces the difficulty and labor intensity of manual operation, while also ensuring the uniformity and efficiency of the reaction, making the reaction process more stable and uniform. In addition, nickel salts and aluminum salts are added to form an electrodeposition solution, and then a cathode and an anode are placed in the electrodeposition solution for electrodeposition, and finally the electrodeposited nickel-based alloy catalyst is dried to obtain a self-supporting nickel-based alloy catalyst.
[0006] The present invention adopts the following technical solutions:
[0007] A method for preparing a self-supporting nickel-based alloy catalyst, the preparation method comprising:
[0008] Step 1: prepare the raw materials and reaction device for the self-supporting nickel-based alloy catalyst. The raw materials for the self-supporting nickel-based alloy catalyst include PVA, nickel nitrate, aluminum nitrate, deionized water and sodium dodecyl sulfate. The PVA is polyvinyl alcohol. The ratio of the raw materials is preset and optimized using an efficient classification optimization model. The reaction device uses an electrochemical synthesis chamber to achieve automatic synthesis and intelligent operation. The efficient classification optimization model includes a data preprocessing module, a feature engineering module, a classifier design module, an integrated learning module and a hyperparameter tuning module:
[0009] The data preprocessing module includes data cleaning, missing value processing, outlier detection and correction, data conversion, and data normalization, with the aim of improving data quality, enhancing model performance, and minimizing the deviation and variance of subsequent learning algorithms;
[0010] The feature engineering module: creates new features and extracts information from raw data to help the model better understand the data and make accurate predictions or classifications;
[0011] The classifier design module is responsible for constructing a mathematical model that can learn from input features and predict the category of unknown data;
[0012] The ensemble learning module: constructs a strong classifier by combining multiple weak classifiers to improve the performance of the model;
[0013] The hyperparameter tuning module aims to find a set of optimal hyperparameters so that the model can obtain the best generalization ability on the validation set;
[0014] Step 2, dissolving the PVA in the deionized water to obtain a PVA aqueous solution, then adding the nickel nitrate to the PVA aqueous solution, stirring the nickel nitrate completely by magnetic stirring, then pouring the mixed solution into a mold, and freeze-drying it to obtain a three-dimensional porous nickel substrate;
[0015] Step 3, preparing an electrodeposition solution: dissolving the nickel nitrate, the aluminum nitrate and the sodium dodecyl sulfate in the deionized water at a predetermined ratio of 1:1:0.15, and fully dissolving them by magnetic stirring to form a uniform electrodeposition solution;
[0016] Step 4: placing a cathode and an anode in the electrodeposition solution for electrodeposition to obtain an alloy nanostructure, wherein the ionic equation for the reduction of nickel ions and aluminum ions on the cathode is:
[0017] Ni 2+ +2e - →Ni (1)
[0018] In formula (1), Ni 2+ is the nickel ion, e - is electron, Ni is nickel element;
[0019] Al 3+ +3e - →Al(2)
[0020] In formula (2), Al 3+ is the aluminum ion, e - is the electron, Al is aluminum element;
[0021] Step 5: taking out the alloy nanostructure obtained in step 4 from the solution, rinsing it with the deionized water, and then placing it in an oven for drying and baking to obtain the self-supporting nickel-based alloy catalyst.
[0022] As a further technical solution of the present invention, the efficient classification optimization model constructs a correlation function of the correlation between the grayscale of the raw material pixel and the self-supporting nickel-based alloy catalyst, and the correlation function is:
[0023]
[0024] In formula (3), F is the correlation of the self-supporting nickel-based alloy catalyst, m is the grayscale of the starting pixel of the preparation raw material, e is the spacing distance between the preparation raw materials, and n is the grayscale of the pixel in a certain angle direction. is the probability of the pixel gray level n in the certain angle direction,
[0025] As a further technical solution of the present invention, the working method of the hyperparameter tuning module in step 1 is to improve on the basis of grid search, adopt random search method, randomly select parameter combinations in the hyperparameter space, and adopt Bayesian optimization method to predict which hyperparameters may lead to better performance by building a probability model, thereby reducing the points that need to be evaluated. The formula is:
[0026] fx)=∫pyXpXdy(4)
[0027] In formula (4), f(x) is the loss on the validation set, p(y|X) is the probability distribution of the loss on the validation set given the hyperparameter X, and p(X) is the prior distribution of the hyperparameter.
[0028] As a further technical solution of the present invention, the raw materials for preparing the self-supporting nickel-based alloy catalyst include 15% of the PVA, 25% of the nickel nitrate, 25% of the aluminum nitrate, 30% of the deionized water and 5% of the sodium dodecyl sulfate.
[0029] As a further technical solution of the present invention, the working method for treating the three-dimensional porous nickel substrate in the step 2 is to first weigh 2.0g of the PVA powder with an analytical balance, slowly add it to a container containing 100mL of the deionized water, place the container at room temperature, and slowly stir it at a speed of 300-400r / min for 2h with a magnetic stirrer until the PVA is completely dissolved to obtain a transparent and viscous PVA aqueous solution, then, add 0.5g of the nickel nitrate to the PVA aqueous solution, continue to use the magnetic stirrer to slowly stir at a speed of 300-400r / min for 30min, pour the mixed solution into the pre-prepared mold, the mold is a polytetrafluoroethylene mold with an internal size of 5cm in length, 5cm in width and 1cm in height, put the mold containing the solution into a freezer, freeze it at -80°C for 24h, and then transfer it to a freeze dryer, dry it under vacuum conditions for 48h, and obtain the three-dimensional porous nickel substrate.
[0030] As a further technical solution of the present invention, the working method of the electrodeposition in step 4 is to place the treated three-dimensional porous nickel substrate as the cathode and the aluminum block as the anode into the electrodeposition solution, turn on the power switch, and apply a voltage of 2.5V-3.0V, so that the nickel ions and aluminum ions in the electrodeposition solution are reduced and deposited on the cathode to form an alloy nanostructure. During the deposition process, the current density is controlled to be 1.5A / dm 2 , the deposition time is 15-20min.
[0031] As a further technical solution of the present invention, the electrochemical synthesis chamber includes an electrolytic cell, a cathode cell, an anode cell, a temperature control system, a sensor and an automatic control system. The electrolytic cell is located in the center of the entire electrochemical synthesis chamber, the cathode cell and the anode cell are located inside the electrolytic cell by welding, the temperature control system is located inside the electrolytic cell by welding through the sensor, and the automatic control system connects the electrolytic cell, cathode cell, anode cell, temperature control system and sensor through cables and communication interfaces, so as to facilitate the collection of various data and regulation.
[0032] As a further technical solution of the present invention, an application of a self-supporting nickel-based alloy catalyst comprises:
[0033] (1) Electrocatalytic hydrogen evolution reaction: The prepared self-supporting nickel-based alloy catalyst is used as a working electrode, a platinum sheet is used as a counter electrode, and a reference electrode is Ag / AgCl, and a HER test is performed in an electrolyte solution (such as 0.5MH2SO4);
[0034] (2) Electrochemical performance test: The HER performance of the catalyst is evaluated by linear sweep voltammetry and electrochemical impedance spectroscopy. In addition, the stability and durability of the catalyst can be evaluated by cyclic voltammetry and chronoamperometry.
[0035] data:
[0036] The linear sweep voltammetry data: In 0.5MH2SO4, the starting potential of the self-supporting nickel-based alloy catalyst is -50mV, reaching 10mA / cm 2 The overpotential required for the current density is 120mV;
[0037] The electrochemical impedance spectroscopy data: the charge transfer resistance of the catalyst is 20 ohms, indicating that it has good charge transfer performance;
[0038] Stability test: After running at a constant potential of 120 mV for 10 h, the current density of the catalyst remained almost unchanged, demonstrating its good stability.
[0039] The present invention discloses a preparation method and application of a self-supporting nickel-based alloy catalyst, which is simple to operate, easy to synthesize on a large scale, and has low cost for non-precious metals; the synthesized catalyst is macroscopically porous and microscopically lamellar, which greatly increases the specific surface area of the catalyst and has extremely high catalytic activity; the self-supporting electrode structure can be directly used in AEM electrolysis of water to produce hydrogen, which is simple and convenient. At the same time, an electrochemical synthesis chamber is used to achieve automatic synthesis and intelligent operation, which greatly reduces the difficulty and labor intensity of manual operation, while also ensuring the uniformity and efficiency of the reaction, making the reaction process more stable and uniform. In addition, nickel salts and aluminum salts are added to form an electrodeposition solution, and then a cathode and an anode are placed in the electrodeposition solution for electrodeposition, and finally the electrodeposited nickel-based alloy catalyst is dried to obtain a self-supporting nickel-based alloy catalyst. BRIEF DESCRIPTION OF THE DRAWINGS
[0040] Figure 1 A flow chart of a method for preparing a self-supporting nickel-based alloy catalyst according to the present invention;
[0041] Figure 2This is a schematic diagram of the proportion of the raw materials in the preparation method of a self-supporting nickel-based alloy catalyst of the present invention;
[0042] Figure 3 This is a schematic diagram of the structure of an electrochemical synthesis chamber in a method for preparing a self-supporting nickel-based alloy catalyst according to the present invention. DETAILED DESCRIPTION
[0043] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0044] Example 1
[0045] A method for preparing a self-supporting nickel-based alloy catalyst, the preparation method comprising:
[0046] Step 1: prepare the raw materials and reaction device for the self-supporting nickel-based alloy catalyst. The raw materials for the self-supporting nickel-based alloy catalyst include PVA, nickel nitrate, aluminum nitrate, deionized water and sodium dodecyl sulfate. The PVA is polyvinyl alcohol. The ratio of the raw materials is preset and optimized using an efficient classification optimization model. The reaction device uses an electrochemical synthesis chamber to achieve automatic synthesis and intelligent operation. The efficient classification optimization model includes a data preprocessing module, a feature engineering module, a classifier design module, an integrated learning module and a hyperparameter tuning module:
[0047] The data preprocessing module includes data cleaning, missing value processing, outlier detection and correction, data conversion, and data normalization, with the aim of improving data quality, enhancing model performance, and minimizing the deviation and variance of subsequent learning algorithms;
[0048] The feature engineering module: creates new features and extracts information from raw data to help the model better understand the data and make accurate predictions or classifications;
[0049] The classifier design module is responsible for constructing a mathematical model that can learn from input features and predict the category of unknown data;
[0050] The ensemble learning module: constructs a strong classifier by combining multiple weak classifiers to improve the performance of the model;
[0051] The hyperparameter tuning module aims to find a set of optimal hyperparameters so that the model can obtain the best generalization ability on the validation set;
[0052] Step 2, dissolving the PVA in the deionized water to obtain a PVA aqueous solution, then adding the nickel nitrate to the PVA aqueous solution, stirring the nickel nitrate completely by magnetic stirring, then pouring the mixed solution into a mold, and freeze-drying it to obtain a three-dimensional porous nickel substrate;
[0053] Step 3, preparing an electrodeposition solution: dissolving the nickel nitrate, the aluminum nitrate and the sodium dodecyl sulfate in the deionized water at a predetermined ratio of 1:1:0.15, and fully dissolving them by magnetic stirring to form a uniform electrodeposition solution;
[0054] Step 4: placing a cathode and an anode in the electrodeposition solution for electrodeposition to obtain an alloy nanostructure, wherein the ionic equation for the reduction of nickel ions and aluminum ions on the cathode is:
[0055] Ni 2+ +2e - →Ni (1)
[0056] In formula (1), Ni 2+ is the nickel ion, e - is electron, Ni is nickel element;
[0057] Al 3+ +3e - →Al(2)
[0058] In formula (2), Al 3+ is the aluminum ion, e - is the electron, Al is aluminum element;
[0059] Step 5: taking out the alloy nanostructure obtained in step 4 from the solution, rinsing it with the deionized water, and then placing it in an oven for drying and baking to obtain the self-supporting nickel-based alloy catalyst.
[0060] In this example, the self-supporting nickel-based alloy catalyst prepared by this method is used as the research object, a high temperature and high pressure reaction apparatus is used to simulate the actual industrial reaction conditions, a hydrogen reduction reaction is used as a probe reaction, and the activity of the catalyst at different temperatures, pressures and times is measured. The experimental data and results are recorded in Table 1.
[0061] Table 1 Performance test results statistics
[0062] Temperature(℃) Pressure(MPa) Reaction time (h) Hydrogen conversion rate (%) 200 1.0 1 50.2 250 1.0 1 75.8 300 1.0 1 92.3 350 1.0 1 87.6 400 1.0 1 78.9
[0063] Through the above performance tests, it can be seen that at 300°C, the hydrogen conversion rate reaches a maximum value of 92.3%, which indicates that the self-supporting nickel-based alloy catalyst prepared by this method exhibits the best catalytic activity at 300°C.
[0064] Example 2
[0065] A method for preparing a self-supporting nickel-based alloy catalyst, the preparation method comprising:
[0066] Step 1: prepare the raw materials and reaction device for the self-supporting nickel-based alloy catalyst. The raw materials for the self-supporting nickel-based alloy catalyst include PVA, nickel nitrate, aluminum nitrate, deionized water and sodium dodecyl sulfate. The PVA is polyvinyl alcohol. The ratio of the raw materials is preset and optimized using an efficient classification optimization model. The reaction device uses an electrochemical synthesis chamber to achieve automatic synthesis and intelligent operation. The efficient classification optimization model includes a data preprocessing module, a feature engineering module, a classifier design module, an integrated learning module and a hyperparameter tuning module:
[0067] The data preprocessing module includes data cleaning, missing value processing, outlier detection and correction, data conversion, and data normalization, with the aim of improving data quality, enhancing model performance, and minimizing the deviation and variance of subsequent learning algorithms;
[0068] The feature engineering module: creates new features and extracts information from raw data to help the model better understand the data and make accurate predictions or classifications;
[0069] The classifier design module is responsible for constructing a mathematical model that can learn from input features and predict the category of unknown data;
[0070] The ensemble learning module: constructs a strong classifier by combining multiple weak classifiers to improve the performance of the model;
[0071] The hyperparameter tuning module aims to find a set of optimal hyperparameters so that the model can obtain the best generalization ability on the validation set;
[0072] Step 2, dissolving the PVA in the deionized water to obtain a PVA aqueous solution, then adding the nickel nitrate to the PVA aqueous solution, stirring the nickel nitrate completely by magnetic stirring, then pouring the mixed solution into a mold, and freeze-drying it to obtain a three-dimensional porous nickel substrate;
[0073] Step 3, preparing an electrodeposition solution: dissolving the nickel nitrate, the aluminum nitrate and the sodium dodecyl sulfate in the deionized water at a predetermined ratio of 1:1:0.15, and fully dissolving them by magnetic stirring to form a uniform electrodeposition solution;
[0074] Step 4: placing a cathode and an anode in the electrodeposition solution for electrodeposition to obtain an alloy nanostructure, wherein the ionic equation for the reduction of nickel ions and aluminum ions on the cathode is:
[0075] Ni 2+ +2e - →Ni (1)
[0076] In formula (1), Ni 2+ is the nickel ion, e - is electron, Ni is nickel element;
[0077] Al 3+ +3e - →Al(2)
[0078] In formula (2), Al 3+ is the aluminum ion, e - is the electron, Al is aluminum element;
[0079] Step 5: taking out the alloy nanostructure obtained in step 4 from the solution, rinsing it with the deionized water, and then placing it in an oven for drying and baking to obtain the self-supporting nickel-based alloy catalyst.
[0080] In a specific embodiment, this embodiment uses the self-supporting nickel-based alloy catalyst (Group A) prepared by the present method and the traditional porous nickel-based electrode (Group B) as research objects, conducts water electrolysis performance test of water electrolysis reaction, constructs two identical electrolytic cells, tests the water electrolysis performance of Group A and Group B respectively, records parameters such as current density, voltage, hydrogen production, and calculates the Faraday efficiency, which is recorded in Table 2.
[0081] Table 2 Comparative statistics of electrolyzed water performance
[0082]
[0083]
[0084] Through the above water electrolysis performance test, the water electrolysis performance of group A and group B can be compared to evaluate the effect of the self-supporting nickel-based alloy catalyst prepared by this method on water electrolysis. From the test results, it can be seen that in terms of hydrogen production and Faraday efficiency, the self-supporting nickel-based alloy catalyst prepared by this method (group A) shows certain advantages over the traditional porous nickel-based electrode (group B), which indicates that the self-supporting nickel-based alloy catalyst prepared by this method can improve the water electrolysis performance.
[0085] Example 3
[0086] In the above embodiment, the efficient classification optimization model constructs a correlation function between the grayscale of the raw material pixel and the correlation of the self-supporting nickel-based alloy catalyst, and the correlation function is:
[0087]
[0088] In formula (3), F is the correlation of the self-supporting nickel-based alloy catalyst, m is the grayscale of the starting pixel of the preparation raw material, e is the spacing distance between the preparation raw materials, and n is the grayscale of the pixel in a certain angle direction. is the probability of pixel gray level n at a certain angle,
[0089] In the above embodiment, the working method of the hyperparameter tuning module in step 1 is to improve on the grid search, adopt a random search method, randomly select parameter combinations in the hyperparameter space, and adopt a Bayesian optimization method to predict which hyperparameters may lead to better performance by building a probability model, thereby reducing the points that need to be evaluated. The formula is:
[0090] fx)=∫pyXpXdy(4)
[0091] In formula (4), f(x) is the loss on the validation set, p(y|X) is the probability distribution of the loss on the validation set given the hyperparameter X, and p(X) is the prior distribution of the hyperparameter.
[0092] In a specific embodiment, in an efficient classification optimization model, a mapping relationship between the grayscale of raw material pixels and the correlation of self-supporting nickel-based alloy catalysts is constructed. In actual production, the proportion of raw materials can be optimized according to this correlation function to obtain a better nickel-based alloy catalyst. The efficient classification optimization model should be based on a certain amount of experimental data to ensure the accuracy and reliability of the model. In addition, the establishment of the optimization model also needs to fully consider the optimization goals in the preparation process, such as improving product performance indicators, reducing raw material costs, etc., to ensure that the obtained optimization scheme can meet multiple optimization goals at the same time.
[0093] The hardware working environment of the efficient classification optimization model includes the following contents:
[0094] 1. Application-specific integrated circuits and field-programmable gate arrays: Improve the speed and efficiency of model classification, process large amounts of data, and reduce data transmission delays between processors and memory.
[0095] 2. Quantum computing hardware: used to process large-scale data sets and complex algorithms.
[0096] 3. Statistical analysis software: used for analysis and optimization calculation of prediction results of self-supporting nickel-based alloy catalyst model, such as Design-Expert, MATLAB and other software.
[0097] 4. Non-volatile memory expressed as solid-state drives: provide higher data throughput and lower latency, speeding up model training and reasoning.
[0098] 5. Efficient network interface card: ensures fast transmission of large amounts of data in a distributed environment.
[0099] 6. Network optimization technology: reduce CPU intervention during data transmission and improve network efficiency, such as RDMA.
[0100] 7. Equipment: Such as liquid cooling systems and energy management systems, which effectively manage the heat generated by the hardware and ensure that the system runs stably under continuous high load.
[0101] In a specific embodiment, the self-supporting nickel-based alloy catalyst prepared by the method is used as a research object, and the catalytic performance of the self-supporting nickel-based alloy catalyst prepared by the method under specific reaction conditions is measured. The catalyst is heated to 500°C in an argon atmosphere and maintained for 2 hours. After pretreatment, the catalyst is placed in a fixed bed reactor, and a mixed gas of hydrogen and carbon monoxide is introduced, starting from 300°C, and gradually heated to 500°C at a rate of 50°C / h, and the data are recorded in Table 3.
[0102] Table 3 Comparative statistics of catalytic performance
[0103] Temperature(℃) Conversion rate (%) Selectivity (%) (mol / g·cat·h) 300 25.3 85.6 0.042 350 48.5 89.3 0.084 400 67.8 92.1 0.132 450 82.6 94.5 0.188 500 90.1 96.2 0.234
[0104] Through the above catalytic performance tests, it can be seen that with the increase of temperature, the conversion rate, selectivity and activity of the catalyst all show an upward trend, which means that under high temperature conditions, the catalytic performance of the catalyst is better exerted and the selectivity of the catalyst is always maintained at a high level, indicating that it has high product selectivity in the catalytic process.
[0105] Example 4
[0106] In the above embodiment, the raw materials for preparing the self-supporting nickel-based alloy catalyst include 15% of PVA, 25% of nickel nitrate, 25% of aluminum nitrate, 30% of deionized water and 5% of sodium dodecyl sulfate.
[0107] In the above embodiment, the working method for treating the three-dimensional porous nickel substrate in the step 2 is to first weigh 2.0g of the PVA powder with an analytical balance, slowly add it to a container containing 100mL of the deionized water, place the container at room temperature, and slowly stir it at a speed of 300-400r / min with a magnetic stirrer for 2h until the PVA is completely dissolved to obtain a transparent and viscous PVA aqueous solution, then, add 0.5g of the nickel nitrate to the PVA aqueous solution, continue to use the magnetic stirrer to slowly stir at a speed of 300-400r / min for 30min, pour the mixed solution into the pre-prepared mold, the mold is a polytetrafluoroethylene mold with an internal size of 5cm in length, 5cm in width and 1cm in height, put the mold containing the solution into a freezer, freeze it at -80°C for 24h, and then transfer it to a freeze dryer, dry it under vacuum conditions for 48h to obtain the three-dimensional porous nickel substrate.
[0108] In the above embodiment, the working method of the electrodeposition in step 4 is to place the treated three-dimensional porous nickel substrate as the cathode and the aluminum block as the anode into the electrodeposition solution, turn on the power switch, and apply a voltage of 2.5V-3.0V, so that the nickel ions and aluminum ions in the electrodeposition solution are reduced and deposited on the cathode to form an alloy nanostructure. During the deposition process, the current density is controlled to be 1.5A / dm 2 , the deposition time is 15-20min.
[0109] In a specific embodiment, the self-supporting nickel-based alloy catalyst prepared by the method is used as a research object, and the catalytic performance of the self-supporting nickel-based alloy catalyst prepared by the method under specific reaction conditions is measured. The catalyst is heated to 500°C in an argon atmosphere and maintained for 2 hours. After pretreatment, the catalyst is placed in a fixed bed reactor, and a mixed gas of hydrogen and carbon monoxide is introduced, starting from 300°C, and gradually heated to 500°C at a rate of 50°C / h, and the data are recorded in Table 4.
[0110] Table 4 Comparative statistics of catalytic performance
[0111]
[0112]
[0113] Through the above catalytic performance tests, it can be seen that with the increase of temperature, the conversion rate, selectivity and activity of the catalyst all show an upward trend, which means that under high temperature conditions, the catalytic performance of the catalyst is better exerted and the selectivity of the catalyst is always maintained at a high level, indicating that it has a high product selectivity in the catalytic process.
[0114] In the above embodiment, the electrochemical synthesis chamber includes an electrolytic cell 1, a cathode cell 2, an anode cell 3, a temperature control system 4, a sensor 5 and an automatic control system 6. The electrolytic cell 1 is located in the center of the entire electrochemical synthesis chamber, and the cathode cell 2 and the anode cell 3 are located inside the electrolytic cell 1 by welding. The temperature control system 4 is located inside the electrolytic cell 1 by welding through the sensor 5. The automatic control system 6 connects the electrolytic cell 1, the cathode cell 2, the anode cell 3, the temperature control system 4 and the sensor 5 through cables and communication interfaces to facilitate the collection of various data and regulation.
[0115] The process of the electrochemical synthesis chamber is exemplified by a specific embodiment below. When the present invention is working, the working method of the electrochemical synthesis chamber is as follows: before starting the electrochemical synthesis chamber, the automatic control system 6 first performs a self-check to ensure that all components are in normal working condition. At the same time, according to the preset synthesis task, the system sets the type, concentration, temperature and other parameters of the electrolyte in the electrolytic cell 1, and adjusts the electrode materials of the cathode cell 2 and the anode cell 3. During the electrochemical synthesis process, the sensor 5 monitors the key parameters such as the temperature, pH value and current density in the electrolytic cell 1 in real time, and transmits the data to the automatic control system 6 in real time. The automatic control system 6 dynamically adjusts the electrolysis parameters such as current intensity and electrolyte flow rate according to the real-time data to ensure the efficiency and stability of the synthesis process. The automatic control system 6 records the changes in all parameters. After the synthesis is completed, the system conducts an in-depth analysis of these data and generates a detailed synthesis report to provide data support for subsequent synthesis tasks. Through the design of the present invention, the electrochemical synthesis chamber realizes the efficiency, stability, safety and reliability of the electrochemical synthesis process through the organic combination of intelligent regulation, dynamic monitoring, energy optimization, data recording and analysis, and safety monitoring and early warning.
[0116] Example 5
[0117] In the above embodiment, a self-supporting nickel-based alloy catalyst is used, and the self-supporting nickel-based alloy catalyst is used including:
[0118] (1) Electrocatalytic hydrogen evolution reaction: The prepared self-supporting nickel-based alloy catalyst is used as a working electrode, a platinum sheet is used as a counter electrode, and a reference electrode is Ag / AgCl, and a HER test is performed in an electrolyte solution (such as 0.5MH2SO4);
[0119] (2) Electrochemical performance test: The HER performance of the catalyst is evaluated by linear sweep voltammetry and electrochemical impedance spectroscopy. In addition, the stability and durability of the catalyst can be evaluated by cyclic voltammetry and chronoamperometry.
[0120] data:
[0121] The linear sweep voltammetry data: In 0.5MH2SO4, the starting potential of the self-supporting nickel-based alloy catalyst is -50mV, reaching 10mA / cm 2 The overpotential required for the current density is 120mV;
[0122] The electrochemical impedance spectroscopy data: the charge transfer resistance of the catalyst is 20 ohms, indicating that it has good charge transfer performance;
[0123] Stability test: After running at a constant potential of 120 mV for 10 h, the current density of the catalyst remained almost unchanged, demonstrating its good stability.
[0124] In a specific embodiment, the self-supporting nickel-based alloy catalyst prepared by the method is used as a research object to evaluate the durability and stability of the self-supporting nickel-based alloy catalyst in practical applications. The sample is cleaned and fixed on the fixture of the universal material testing machine, and the parameters such as the loading speed and the loading range are set. The universal material testing machine is started, and a gradually increasing external force is applied to the sample, and the results are recorded in Table 5.
[0125] Table 5 Mechanical strength test statistics
[0126] index Numeric Elastic modulus(GPa) 200.0 Yield strength (MPa) 1000.0 Breaking strength(MPa) 1200.0
[0127] The experimental results are shown in Table 5. It can be seen from the test data that the self-supporting nickel-based alloy catalyst prepared by this method has high mechanical strength and can meet the needs of practical applications.
[0128] Although the specific embodiments of the present invention are described above, it should be understood by those skilled in the art that these specific embodiments are only illustrative, and those skilled in the art may omit, replace, and change the details of the above methods and systems in various ways without departing from the principles and essence of the present invention. For example, merging the above method steps so as to perform substantially the same functions in substantially the same manner to achieve substantially the same results is within the scope of the present invention. Therefore, the scope of the present invention is limited only by the appended claims.
Claims
1. A method for preparing a self-supporting nickel-based alloy catalyst, characterized in that: The preparation method comprises: Step 1: prepare the raw materials and reaction device for the self-supporting nickel-based alloy catalyst. The raw materials for the self-supporting nickel-based alloy catalyst include PVA, nickel nitrate, aluminum nitrate, deionized water and sodium dodecyl sulfate. The PVA is polyvinyl alcohol. The ratio of the raw materials is preset and optimized using an efficient classification optimization model. The reaction device uses an electrochemical synthesis chamber to achieve automatic synthesis and intelligent operation. The efficient classification optimization model includes a data preprocessing module, a feature engineering module, a classifier design module, an integrated learning module and a hyperparameter tuning module: The data preprocessing module includes data cleaning, missing value processing, outlier detection and correction, data conversion, and data normalization, with the aim of improving data quality, enhancing model performance, and minimizing the deviation and variance of subsequent learning algorithms; The feature engineering module: creates new features and extracts information from raw data to help the model better understand the data and make accurate predictions or classifications; The classifier design module is responsible for constructing a mathematical model that can learn from input features and predict the category of unknown data; The ensemble learning module: constructs a strong classifier by combining multiple weak classifiers to improve the performance of the model; The hyperparameter tuning module aims to find a set of optimal hyperparameters so that the model can obtain the best generalization ability on the validation set; Step 2, dissolving the PVA in the deionized water to obtain a PVA aqueous solution, then adding the nickel nitrate to the PVA aqueous solution, stirring the nickel nitrate completely by magnetic stirring, then pouring the mixed solution into a mold, and freeze-drying it to obtain a three-dimensional porous nickel substrate; Step 3, preparing an electrodeposition solution: dissolving the nickel nitrate, the aluminum nitrate and the sodium dodecyl sulfate in the deionized water at a predetermined ratio of 1:1:0.15, and fully dissolving them by magnetic stirring to form a uniform electrodeposition solution; Step 4: placing a cathode and an anode in the electrodeposition solution for electrodeposition to obtain an alloy nanostructure, wherein the ionic equation for the reduction of nickel ions and aluminum ions on the cathode is: ; In formula (1), is the nickel ion, For electronics, It is nickel element; ; In formula (2), is the aluminum ion, For the electron, It is a single substance of aluminum; Step 5, taking out the alloy nanostructure obtained in the step 4 from the solution, rinsing it with the deionized water, and then drying it in an oven to obtain the self-supporting nickel-based alloy catalyst; The working method of the electrodeposition in step 4 is to place the treated three-dimensional porous nickel substrate as the cathode and the aluminum block as the anode into the electrodeposition solution, turn on the power switch, and apply a voltage of 2.5V-3.0V so that the nickel ions and aluminum ions in the electrodeposition solution are reduced and deposited on the cathode to form an alloy nanostructure. During the deposition process, the current density is controlled to be 1.5A / dm 2 , the deposition time is 15-20min.
2. The method for preparing a self-supporting nickel-based alloy catalyst according to claim 1, characterized in that: The efficient classification optimization model constructs a correlation function between the grayscale of the raw material pixel and the correlation of the self-supporting nickel-based alloy catalyst, and the correlation function is: ; In formula (3), Correlation for the self-supporting nickel-based alloy catalyst, is the grayscale of the starting pixel point of the raw material preparation, is the spacing distance between the preparation raw materials, is the grayscale of the pixel at a certain angle, is the grayscale of the pixel at the certain angle direction The probability of , , , .
3. The method for preparing a self-supporting nickel-based alloy catalyst according to claim 1, characterized in that: The working method of the hyperparameter tuning module in step 1 is to improve on the grid search, adopt random search method, randomly select parameter combinations in the hyperparameter space, and adopt Bayesian optimization method to predict which hyperparameters may lead to better performance by building a probability model, thereby reducing the points that need to be evaluated. The formula is: ; In formula (4), is the loss on the validation set, is the probability distribution of loss on the validation set given the hyperparameters X, is the prior distribution of the hyperparameters.
4. The method for preparing a self-supporting nickel-based alloy catalyst according to claim 1, characterized in that: The raw materials for preparing the self-supporting nickel-based alloy catalyst include 15% of PVA, 25% of nickel nitrate, 25% of aluminum nitrate, 30% of deionized water and 5% of sodium dodecyl sulfate.
5. The method for preparing a self-supporting nickel-based alloy catalyst according to claim 1, characterized in that: The working method for treating the three-dimensional porous nickel substrate in the step 2 is to first weigh 2.0g of the PVA powder with an analytical balance, slowly add it to a container containing 100mL of the deionized water, place the container at room temperature, and slowly stir it at a speed of 300-400r / min for 2h with a magnetic stirrer until the PVA is completely dissolved to obtain a transparent and viscous PVA aqueous solution, then add 0.5g of the nickel nitrate to the PVA aqueous solution, continue to use the magnetic stirrer to slowly stir at a speed of 300-400r / min for 30min, pour the mixed solution into the pre-prepared mold, the mold is a polytetrafluoroethylene mold with an internal size of 5cm in length, 5cm in width and 1cm in height, put the mold containing the solution into a freezer, freeze it at -80°C for 24h, and then transfer it to a freeze dryer, dry it under vacuum conditions for 48h to obtain the three-dimensional porous nickel substrate.
6. The method for preparing a self-supporting nickel-based alloy catalyst according to claim 1, characterized in that: The electrochemical synthesis chamber comprises an electrolytic cell (1), a cathode cell (2), an anode cell (3), a temperature control system (4), a sensor (5) and an automatic control system (6); the electrolytic cell (1) is located at the center of the entire electrochemical synthesis chamber; the cathode cell (2) and the anode cell (3) are located inside the electrolytic cell (1) by welding; the temperature control system (4) is located inside the electrolytic cell (1) by welding through the sensor (5); and the automatic control system (6) is connected to the electrolytic cell (1), the cathode cell (2), the anode cell (3), the temperature control system (4) and the sensor (5) by cables and communication interfaces, so as to facilitate the collection of various data and regulation.
7. Use of a self-supporting nickel-based alloy catalyst prepared by the method for preparing a self-supporting nickel-based alloy catalyst according to any one of claims 1 to 6, characterized in that: include: (1) Electrocatalytic hydrogen evolution reaction: The prepared self-supporting nickel-based alloy catalyst was used as the working electrode, the platinum sheet was used as the counter electrode, and the reference electrode was Ag / AgCl, and the HER test was carried out in a 0.5MH2SO4 electrolyte solution; (2) Electrochemical performance testing: The HER performance of the catalyst was evaluated by linear sweep voltammetry and electrochemical impedance spectroscopy. In addition, the stability and durability of the catalyst were evaluated by cyclic voltammetry and chronoamperometry; The data includes: The linear sweep voltammetry data: In 0.5MH2SO4, the starting potential of the self-supporting nickel-based alloy catalyst is -50mV, reaching 10mA / cm 2 The overpotential required for the current density is 120 mV; The electrochemical impedance spectroscopy data: the charge transfer resistance of the catalyst is 20 ohms, indicating that it has good charge transfer performance; Stability test: After running at a constant potential of 120 mV for 10 h, the current density of the catalyst remained almost unchanged, demonstrating its good stability.
Citation Information
Patent Citations
Preparation method of nickel-based alloy electrolysis hydrogen evolution cathode porous material
CN108247060A
Method for preparing high-performance self-supporting catalytic electrode through ammonium fluoride assisted electro-deposition
CN117239147A
